Devotees worshipping the Mukhalingam in the procession - Mumbai Archive Project Team (Jio Institute, 2024)
Devotees stand in line for hours to observe the darshan of the procession. Darshan is based on the philosophical concept of Advaita (non-duality), where the devotee and the divine are seen as one. Darshan is thus a realization of this oneness. It is believed that through darshan, devotees establish a direct connection with the divine, experiencing a sense of peace and spiritual fulfilment.